HIV-infected patients rarely develop invasive fungal diseases under good immune reconstitution after ART regardless high prevalence of pathogenic filamentous fungi carriage in nasopharynx/oropharynx - Chen, Xiaoman; Cao, Yi; Chen, Meijun; Wang, Haodi; Du, Peishan; Li, Hong; Zhong, Huolin; Li, Quanmin; Zhao, Santao; Yao, Zhenjiang; Chen, Wanshan; Cai, Weiping; et al. (Frontiers in Microbiology, 2022)
Purpose: We aimed to investigate the prevalence and risk factors of filamentous fungi (FF) carriage in human immunodeficiency virus (HIV)-infected patients in Guangdong province, along with its subsequent incidence of invasive fungal disease (IFD). Methods: Seven hundred and sixteen HIV-infected individuals from the outpatient clinic and 293 sex-matched healthy controls were recruited prospectively from May 1 to August 31, 2017. Fungi were isolated from oropharyngeal and nasopharyngeal swabs, then identified by morphological and molecular biological techniques. Logistic regression analysis was used to identify risk factors of pathogenic FF carriage. Pathogenic FF carriers were followed up through the end of 2019. Results: Of the 716 included HIV-infected patients, 602 (84.1%) were male, the median age was 34 (27-42) years, and the median CD4+ count was 385 (254-542) cells/μL. Pathogenic FF were isolated in 119 (16.62%) cases with HIV infection and 40 (13.65%) healthy controls. Mucorales were found in 3 HIV-infected individuals and Talaromyces marneffei in 2 HIV-infected individuals, but not in healthy controls. History of cured opportunistic infections (OIs) (OR, 1.97; 95% CI, 1.23-3.13, P =0.004), and smoking (OR, 1.55; 95%CI, 1.03-2.32, P =0.035) were independent risk factors of pathogenic FF carriage in HIV-infected individuals. A total of 119 pathogenic FF carriers with HIV infection were followed. During follow-up, 119 (100%) cases received antiretroviral therapy (ART) for at least 28 months, 107 (90%) cases had CD4+ counts>200 cells/μL, and none developed IFD. Discussion: Pathogenic FF carriage is common in HIV-infected individuals but may not develop IFD in those who achieved immune reconstitution. Smoking and cured OIs history increase the risk of pathogenic FF carriage. Smoking abstinence and ART adherence are especially important for these patients.